Survival of contagious ovine digital dermatitis (CODD)‐associated treponemes on disposable gloves after handling CODD‐affected feet. (22nd July 2017) - Angell, J. W.; Clegg, S. R.; Grove‐White, D. H.; Blowey, R. W.; Carter, S. D.; Duncan, J. S.; Evans, N. J.
Abstract : Both contagious ovine digital dermatitis (CODD) and bovine digital dermatitis (BDD) are causes of infectious lameness in sheep and cattle, respectively, and are strongly associated with the presence of specific treponemes, with three different cultivable phylogroups commonly isolated: Treponema medium, Treponema phagedenis and Treponema pedis . The aim of this study was to investigate the potential to transmit CODD‐associated Treponema species via gloves used when handling visibly clinically affected animals. The feet of sheep with and without CODD were handled as part of routine examination with gloved hands. The gloves were then swabbed to detect the presence of treponemes immediately after handling. Detection methods included culture and isolation techniques together with DNA detection by PCR. In addition, the duration of survival in air was determined as well as the efficacy of common disinfectants to remove treponemes from gloves. In this study, we demonstrate that CODD‐associated treponemes can survive on gloves used to handle the feet of CODD‐affected sheep but may be removed effectively using common disinfectants. These data provide evidence of a potential route of transmission and identify a practical method to reduce this risk.